Fresh Properties and Flexural Strength of 3D Printing Concrete Containing GGBS with Varies in Water-Cement Ratio - Kevin Ooi Chin Kai; Ali, Noorwirdawati; Abdullah, Siti Radziah; Salleh, Norhafizah; Abdul Hamid, Noor Azlina (Journal of Structural Monitoring and Built Environment, 2022)
In the recent years of construction industry, the need of 3D printing technologies start to booming throughout the global and significant progress has been achieved in the development of large scale of 3D printing industry. The use of 3D concrete printing to produce structural components and buildings is extremely feasible. Freeform of building is allowed in 3D concrete printing without the necessity of high cost of formwork, which has big advantage over traditional method of pouring concrete into formwork. The aim to conduct this study is to investigate the flexural strength of 3D Printing Concrete contain Ground Granulated Blast Furnace- Slag (GGBS) with varies in water-cement ratio and its fresh properties. The percentage of GGBS that used to replace the Portland cement in this study is 30% because GGBS has various benefit compare to traditional cement. The main goal of this experiment is to determine the amount of water required for cement contained with GGBS as partial cement replacement which will benefit to the largescale 3D printing technology. The water-cement ratio varied from 0.4-0.6 with 0.05 increment. The findings of this study shown that the fresh properties of the mixture increased with the increment of water-cement ratio while the hardened properties, flexural strength decreased with the increment of water-cement ratio.